Behring's Sea and Arctic Ocean from surveys of the U.S. North Pacific Surveying Expedition in 1855 / Commander John Rodgers, U.S.N., Commanding and from Russian and English authorities - United States North Pacific Exploring Expedition (1853-1856) (Washington, D.C. : United States Hydrographic Office, 1868)
Relief shown by hachures and spot heights. Depths shown by soundings. Grayscale; 1:4,400,000